Automated dynamic sepsis surveillance with routine data: opportunities and challenges - Lindner, Holger A.; Thiel, Manfred; Schneider-Lindner, Verena (Annals of translational medicine, 2017)
Clinicians face an ever-increasing workload due to rising medical complexity of their patients, particularly in the intensive care unit (ICU). Difficulty in keeping abreast of the current clinical situation of critically ill patients with strongly fluctuating health state is augmented by abundance of information from vital signs, laboratory tests, and imaging studies. Rising pressure also comes from cost constraints and performance measurement. Advances in health information technology drive standards and demands, in turn, adding to the pressure. At the same time, mining of medical information in critical care still holds great potential in supporting clinical decision making.
Gesehen am 08.10.2018